Ability of Laying Hens to Distinguish Between Companions According to Their Success in Gaining Access to Food - Wichman, Anette (Frontiers in Veterinary Science, 2018)
Laying hens (Gallus gallus) are social birds with cognitive abilities related to having a functional interaction with their peers. Gaining knowledge about for example new food sources from other individuals can be a valuable complement to individual learning and probably even more so if one copy the behaviour of successful individuals. In this study the aim was to investigate if a bird would identify another bird as being successful at gaining access to food. A social food learning test was developed where birds could move freely together between several scattered food sources. Two different methods were used for training. In method 1, the observer hens were either exposed to a successful demonstrator hen that gained access to the food sources and an unsuccessful demonstrator hen (that gained no access to food) at the same time when trained together in a trio. In method 2, the observer was trained in two different pair constellations, with a successful and unsuccessful demonstrator, respectively. After the training it was evaluated how much the observer birds followed the two different demonstrators to the food sources in a test situation in the same setting where no food was available for any bird. Observers that had been trained in pairs (method 2) showed more following behaviour towards the successful demonstrators than the unsuccessful demonstrator (P=0.005), but observers trained in trios (method 1) did not show any difference in following behaviour between successful and unsuccessful demonstrator. Thus the results indicate that laying hens are able to use another bird as a cue of whether they will get access to food.